Suspended organic matter in the Barents Sea. - Romankevich, Evgeny A; Korneeva, Galina A; Shevchenko, Vladimir P; Gordeev, Vladimir Yu; Belyaev, Nikolay A (PANGAEA, 2000)
A comparative estimation of particulate organic matter concentration in seawater in various regions of the Barents Sea was carried out on the basis of materials collected by authors in August-September 1997. It is shown that the major feature of near-bottom distribution of particulate organic matter is distinct decrease in its concentration from off-shore areas of the Murman and Novaya Zemlya coasts and the Franz Josef Land Archipelago toward the central part of the Barents Sea. Using a method of mean and maximum concentrations of particulate organic matter, an attempt was made to estimate its fluxes from the surface to the bottom.
(Table 2) Particulate organic carbon concentrations in the water column of the Barents Sea in August-September 1997
Keywords: Akademik Sergey Vavilov; Archive of Ocean Data; ARCOD; ASV11; ASV11-830P; ASV11-835P; ASV11-838P; ASV11-841P; ASV11-847P; ASV11-856P; ASV11-860P; ASV11-861P; ASV11-869P; ASV11-875P; ASV11-877P; ASV11-880P; ASV11-891P; ASV11-894P; ASV11-897P; Barents Sea; Carbon, organic, particulate; Carbon analyser AN-7529, 7560; Date/Time of event; DEPTH, water; Mixed layer, thickness; MULT; Ratio